Covariance of Sun and Shade Leaf Traits Along a Tropical Forest Elevation Gradient - Martin, Roberta E.; Asner, Gregory P.; Bentley, Lisa Patrick; Shenkin, Alexander; Salinas, Norma; Huaypar, Katherine Quispe; Pillco, Milenka Montoya; Ccori Álvarez, Flor Delis; Enquist, Brian J.; Diaz, Sandra; Malhi, Yadvinder (Frontiers in Plant Science, 2020)
Foliar trait adaptation to sun and shade has been extensively studied in the context of photosynthetic performance of plants, focusing on nitrogen allocation, light capture and use via chlorophyll pigments and leaf morphology; however, less is known about the potential sun-shade dichotomy of other functionally important foliar traits. In this study, we measured 19 traits in paired sun and shade leaves along a 3,500-m elevation gradient in southern Peru to test whether the traits differ with canopy position, and to assess if relative differences vary with species composition and/or environmental filters. We found significant sun-shade differences in leaf mass per area (LMA), photosynthetic pigments (Chl ab and Car), and δ13C. Sun-shade offsets among these traits remained constant with elevation, soil substrates, and species compositional changes. However, other foliar traits related to structure and chemical defense, and those defining general metabolic processes, did not differ with canopy position. Our results suggest that whole-canopy function is captured in many traits of sun leaves; however, photosynthesis-related traits must be scaled based on canopy light extinction. These findings show that top-of-canopy measurements of foliar chemistry from spectral remote sensing approaches map directly to whole-canopy foliar traits including shaded leaves that cannot be directly observed from above.